Sex Differences in body fluid and electrolyte homeostasis: sex chromosome complement influences on angiotensin responses - Vivas, Laura (2015)
Fil: Vivas, Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigación Médica Mercedes y Martín Ferreyra: Argentina.